LEGAL BASIS FOR REPORTING EMBEZZLEMENT OF MOTORIZED VEHICLES (OBJECTS OF FIDUCIARY GUARANTEES) TRANSFERRED TO THIRD PARTIES BY FIDUCIARIES WITH PAWNING - ARI TRI WIBOWO (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2023)
This research aims to analyze the validity of the pledge agreement for fiduciary collateral objects and also how the fiduciary object is reported to be embezzled by the fiduciary object regarding fiduciary objects transferred by him to a third party. The research method used was normative legal research, with the main data source using secondary data, analyzed normatively qualitatively. This research was conducted because of many cases occurring related to the transfers of fiduciary objects without the consent of fiduciary recipient by fiduciary grantor, leading to such disputes as the embezzlement of fiduciary objects and most people not knowing how to resolve the dispute through legal channels. This research found that the validity of a pawn agreement on fiduciary collateral objects is determined by the preparation of a notarial and registered fiduciary security deed as well as a transfer having received written permission from the fiduciary grantor, then the reporting of fiduciary object embezzlement can be done by the fiduciary grantor based on Article 372 of the Criminal Code (KUHP) rather than on Article 36 of the Fiduciary Law.Keywords: Fiduciary; Embezlement; Motor Vehicles; Guarantee.